Voice of the Poor in the Middle Ages : an Anthology of Documents from the Cairo Geniza. - Cohen, Mark R. (Princeton University Press, 2013)
They are voices that have been silent for centuries: those of captives and refugees, widows and orphans, the blind and infirm, and the underclass of the ""working poor."" Now, for the first time, the voices of the poor in the Middle Ages come to life in this moving book by historian Mark Cohen. A companion to Cohen's other volume, Poverty and Charity in the Jewish Community of Medieval Egypt, the book presents more than ninety letters, alms lists, donor lists, and other related documents from the Geniza, a hidden chamber for discarded papers, situated inside a wall in a Cairo synagogue. Cohen.